Smart Specialisation in less-developed regions of the European Union: A Systematic Literature Review - Wibisono, Eristian (REGION, 2022)
This paper reviews the literature on Smart Specialization implementation in less developed regions of the European Union (EU). Using a systematic literature review research protocol, I critically explore the content of selected relevant papers, examine the challenges in the Smart Specialization implementation in less developed regions of the EU, and raise critical factors that could potentially enhance the success of its implementation. The first finding of this study shows that research on related topics published in leading journals has increased significantly in recent years. Furthermore, as an essential contribution, I categorize the selected papers according to diversity in research design and methodology. Finally, I summarise three key issues of Smart Specialization implementation in less developed regions of the EU: RIS capacity and governance, local and extra-regional collaboration, and regional administrative and financial governance.